2023
DOI: 10.7759/cureus.48960
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive-Compulsive Disorder (OCD): A Comprehensive Review of Diagnosis, Comorbidities, and Treatment Approaches

Abhimanyu Singh,
Vaibhav P Anjankar,
Bhagyesh Sapkale

Abstract: Obsessive-compulsive disorder (OCD) is a neuropsychiatric disorder widely recognized for its recurrent obsessions and compulsions, which may cause severe impairment worldwide. This review explores the difficulties in diagnosing OCD, its comorbidities, and its treatment approaches. Psychiatry and neuroscience face noteworthy obstacles in treating OCD, which is frequently misdiagnosed and inadequately addressed. This illness, which causes upsetting symptoms that interfere with day-to-day living, affects not only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…It started improving following the first infusion: depression: 15 (moderate), anxiety: 3 (normal), and stress: 4 (normal) two hours after ketamine administration. After a transient deterioration (the stressful academic news regarding academic examination), further improvement was observed with a subsequent second and third infusion to a minimum level (3)(4)(5). This minimum DASS-21 score was sustained during discharge and follow-up at the sixth and 12 th weeks (Table 4).…”
Section: Infusion Proceduresmentioning
confidence: 93%
See 3 more Smart Citations
“…It started improving following the first infusion: depression: 15 (moderate), anxiety: 3 (normal), and stress: 4 (normal) two hours after ketamine administration. After a transient deterioration (the stressful academic news regarding academic examination), further improvement was observed with a subsequent second and third infusion to a minimum level (3)(4)(5). This minimum DASS-21 score was sustained during discharge and follow-up at the sixth and 12 th weeks (Table 4).…”
Section: Infusion Proceduresmentioning
confidence: 93%
“…Obsessive-compulsive disorder (OCD) is a chronic waxing and waning disorder characterized by recurrent intrusive, upsetting, and unwanted thoughts (called obsessions) and/or ritualized, repetitive behaviors (called compulsions), which are usually performed to reduce the anxiety that the obsessions cause [ 1 - 3 ]. OCD is also considered a neuropsychiatric disease [ 3 ]. World Health Organization (WHO) reported that OCD is one of the top 10 most incapacitating illnesses [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Severe consequences can occur as a result of misidentification for patients—such as the cited case of a woman who lost custody of her children for 5 months following disclosure of intrusive, ego-dystonic thoughts of infant harm without intent (Vollers, 2020), despite the nearly universal prevalence of harming intrusions in the postpartum period (Brok et al, 2017). OCD can be commonly misdiagnosed as depression in the postpartum period given the lack of awareness of childbirth as a trigger for obsessive–compulsive symptoms and the overlap between depressive ruminations and obsessions (Grant, 2014; Singh et al, 2023). It is also not uncommon for severe cases of OCD to be mistaken for a psychotic disorder (Rohanachandra & Vipulanandan, 2019; Shad Mujeeb, 2017).…”
mentioning
confidence: 99%